Zerumbone inhibits prostate cancer cell viability and induces cell death by non-apoptotic pathway - Cao, Xian-De; Zheng, Hui-Min (Bangladesh Journal of Pharmacology, 2016)
The aim of the present study was to investigate the role of zerumbone on the proliferation, cell cycle arrest and cell death in DU-145 prostate cancer cell lines. The MTT assay revealed that zerumbone (20 µM) reduced proliferation of DU-145 cells to 39.0% at 48 hours. It also increased the proportion of propidium iodide stained cells to 53.4% compared 1.0% in control. However, the population of annexin V-stained cells remained uneffected indicating induction of non-apoptotic cell death by zerumbone. Treatment of DU-145 cells with zerumbone (20 µM) caused 8-fold enhancement in the level of reactive oxygen species (ROS). On the other hand, exposure of the zerumbone treated DU-145 cells to glutathione inhibited the generation of ROS. Fow cytometry using propidium iodide staining revealed that zerumbone treat-ment increased proportion of cells in G1 phase to 71.3% on compared to 34.7% in the control. The results from Western blot analysis revealed a significant increase in the expression of cyclin D1 protein in DU-145 cells on treatment with 20 µM concentration of zerumbone. Thus, zerumbone treatment inhibits prostate cancer cell viability and can be used for its treatment. Video Clip of Methodology: Western blot assay: 3 min 37 sec Full Screen Alternative